IMPLEMENTASI PEMIKIRAN DIGITALISASI DAN FUTURISTIK DALAM PEMBELAJARAN MATEMATIKA DI SD - Jusar, Ira Rahmayuni; Ambiyar, Ambiyar; Aziz, Ishak (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The digital era is the division of the economy caused by technological developments that refer to opportunities that impact education. This influence is called digitization in the learning process. The method used is a literature study by reviewing ten articles in national journals and then analyzing them according to the indicators of this study, namely digitization and futuristics. The results showed that (1) Learning is not limited by time and space; (2) Ease of obtaining information not only by teachers and students but also everyonel (3) Education requires learning to follow the development of innovative and creative technology to produce curriculum updates and other learning tools. One example of technological growth in line with futuristic thinking that can apply to mathematics learning in elementary schools is the application of GeoGebra, which can assist students in visualizing the mathematical learning process and tools for teachers in providing geometry to students.